Effects of viscous dissipation over an unsteady stretching surface embedded in a porous medium with heat generation and thermal radiation - Falana, Ayodeji; Oluyemi Owoeye, Samuel; Abideen Yussouff, Abiodun; Ademola Mumuni, Quadri (Zielona Góra: Uniwersytet Zielonogórski)
This work analyzes the impact of viscous dissipation on an unstable stretching surface in a porous medium with heat generation and thermal radiation-an important factor for numerous engineering applications like cooling baths and plastic sheets. Using MATLAB`s Runge-Kutta fourth-order approach, the controlling partial differential equations are converted into highly nonlinear ordinary differential equations that can be solved numerically.
Keywords: heat generation; porous medium; thermal radiation; unsteady stretching surface; viscous dissipation